PERTOBATAN DIALOGIS - Imanuel Teguh Harisantoso (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
The word "dog" in Mark 7:24-30 is characterized by colonizing, dictators, and feudal who want to separate a person on a social, religious, and racial basis. The postcolonial study is the right approach to uncover the complicated of Jesus ' experience with the Syro-Phoenician woman, remembering that the Gospel of Mark was written during the turbulent time of colonial politics, circa 70 CE. The text and context of Mark become integral to the colonization process. The authority of Jesus symbolically as ruler acted superior over the Syro-Phoenician woman, weak and unclean. The authoritative rule over the weak produces stereotypical prejudices and presumptions. At first, they view each other from different places, from their perspective cultural perception rooms, searching for the exact meeting point and establishing bilateral agreements. In the end, they recognize one another, which resulted in repentance.